2016
DOI: 10.1136/bmjopen-2016-011495
|View full text |Cite
|
Sign up to set email alerts
|

Combined cognitive–behavioural and mindfulness programme for people living with dystonia: a proof-of-concept study

Abstract: ObjectivesTo design and test the delivery of an intervention targeting the non-motor symptoms of dystonia and pilot key health and well-being questionnaires in this population.DesignA proof-of-concept study to test the delivery, acceptability, relevance, structure and content for a 3-day group residential programme for the management of dystonia.SettingParticipants were recruited from a single botulinum toxin clinic. The intervention was delivered in the community.Participants14 participants consented to take … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…To date, there has only been one proof-of-concept study investigating the benefits of CBT in patients with dystonia (n = 9). This cohort underwent a course of CBT combined with mindfulness following which anxiety, depression, and wellbeing scores were improved, with this effect sustained for up to 3 months post-completion of the course together with additional improvements in dystonia severity [12]. This evidence demonstrates the potential benefit of CBT for patients with dystonia for both psychological difficulties and other symptoms associated with the disorder, as well as the importance of further research into this area.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…To date, there has only been one proof-of-concept study investigating the benefits of CBT in patients with dystonia (n = 9). This cohort underwent a course of CBT combined with mindfulness following which anxiety, depression, and wellbeing scores were improved, with this effect sustained for up to 3 months post-completion of the course together with additional improvements in dystonia severity [12]. This evidence demonstrates the potential benefit of CBT for patients with dystonia for both psychological difficulties and other symptoms associated with the disorder, as well as the importance of further research into this area.…”
Section: Discussionmentioning
confidence: 80%
“…CBT has been shown to be particularly effective in the management of the psychiatric symptoms frequently observed in cervical dystonia [ 10 , 11 ], with a recent feasibility study demonstrating the ability for face-to-face CBT combined with mindfulness to substantially reduce depression and anxiety scores using standardised questionnaires [ 12 ]. Unfortunately, timely access to face-to-face psychological therapy is often limited due to cost, waiting times, a shortage of suitably qualified therapists and the stigma associated with psychological therapy.…”
Section: Introductionmentioning
confidence: 99%
“…A review of behavioural interventions for adult onset primary dystonia [62] similarly concluded that more quality research is needed, but that there is reason to believe that behavioural interventions could assist selfmanagement of dystonia outside clinical settings. An example of such a programme was piloted by Sandhu et al [63], who concluded that a combined cognitive behavioural and mindfulness programme could assist self-management and an integrated approach to managing the psychosocial impact of dystonia.…”
Section: Dealing With Self-doubt and Alienationmentioning
confidence: 99%
“…Adverse life events involving loss, identified as specific precipitants of depression, are prominent in dystonic patients. Depression in dystonia can be triggered by lack of satisfaction with social support, maladaptive coping strategies, self-depreciation, and altered body concept [8,32,35]. The disability and pain induced by the motor disorder may act as a nonspecific stressor and combine with other factors to induce depression [8].…”
Section: Epidemiological and Etiological Basismentioning
confidence: 99%
“…If antidepressant therapy worsens dystonia, changing to a different class of drug, or adding in an anticholinergic may, minimize, or prevent exacerbation of dystonia [8]. Cognitive-behavioral therapy (CBT) might ameliorate depression in dystonia patients by altering maladaptive coping strategies that contribute to the mood disorder [35].…”
Section: Treatment Optionsmentioning
confidence: 99%